Structural condition assessment of existing structures in Western Australia: A review of guidelines and building licence initiation - Waller, A.; Vimonsatit, Vanissorn (Engineers Media Pty Ltd, 2012)
Australian built environment is constantly expanding and a review of the methods and guidelines used to assess existing structures is required to ensure the safety of the structure and its occupants. This paper reviews the current Australian guideline for the assessment of an existing structure (AS ISO 13822) and compares it to the guideline used in the United States of America. The analysis of the Australian guideline yielded three possible areas of improvement. A hypothesis on the introduction of building licence was set which would account for and improve these areas. A case study was carried out with the Thai Building Control Act, B.E 2522, Section 32. This Act outlined the introduction of compulsory structural assessments. Interviews with key professional members in the assessment industry were conducted to seek industrial opinions on the regulated assessment initiation and changes that would need to be made for a successful implementation.